Penguatan Karakter Gotong Royong Melalui Pembelajaran Diskursus Multy Reprecentacy Di Sekolah Dasar - Atnuri Atnuri (EduStream: Jurnal Pendidikan Dasar, 2018)
Teachers who do not understand the concept of character education cultivation. In fact educators only write down the characters that must be fulfilled by students without giving examples and explain them first. This study aims to determine the process of applying the Discourse Multi Reprecentacy (DMR) learning model assisted by pokari media (caricature pop up) in strengthening the character of mutual cooperation and to determine whether or not the influence of the DMR learning model of pokari media assisted (pop up caricatures) in strengthening the character of mutual cooperation. This research is a quantitative descriptive study using the Nonequivalent Control Group Design research design. Research samples of class III-A and III-B students, using the Sampling Purposive technique. Data collection techniques use observations of educators and students. This data analysis technique uses percentages and t-tests. The results of this study indicate that (1) the activities of educators and students using the DMR learning model assisted by pokari media (caricature pop up) are categorized well. (2) the results of the hypothesis test show that ttable â‰¤ t_calculate which means there is an influence of the learning model DMR assisted by pokari media (caricature pop up) in strengthening the character of mutual cooperation.